2002
DOI: 10.1093/emboj/21.4.572
|View full text |Cite
|
Sign up to set email alerts
|

Conserved properties of hydrogenosomal and mitochondrial ADP/ATP carriers: a common origin for both organelles

Abstract: Mitochondria are one of the hallmarks of eukaryotic cells, exporting ATP in exchange for cytosolic ADP using ADP/ATP carriers (AAC) located in the inner mitochondrial membrane. In contrast, several evolutionarily important anaerobic eukaryotes lack mitochondria but contain hydrogenosomes, peculiar organelles of controversial ancestry that also supply ATP but, like some fermentative bacteria, make molecular hydrogen in the process. We have now identi®ed genes from two species of the hydrogenosome-containing fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 57 publications
1
68
0
Order By: Relevance
“…The Hmp31 protein has up to 52% similarity to yeast mitochondrial carrier family proteins and therefore was likely to have conserved membrane-targeting signals recognized by the mitochondrial protein translocation machinery (18,56). Recently, a related mitochondrial carrier family protein, the hydrogenosomal ADP/ATP carrier from the fungus Neocallimastix, which has Ͼ90% similarity with its yeast counterparts, was successfully imported in vivo into yeast mitochondria and restored an ADP/ATP carrier-deficient strain (8). In the present study, we show that a hydrogenosomal protein with no homology to any reported protein from yeast was expressed stably in yeast and was targeted to its mitochondria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Hmp31 protein has up to 52% similarity to yeast mitochondrial carrier family proteins and therefore was likely to have conserved membrane-targeting signals recognized by the mitochondrial protein translocation machinery (18,56). Recently, a related mitochondrial carrier family protein, the hydrogenosomal ADP/ATP carrier from the fungus Neocallimastix, which has Ͼ90% similarity with its yeast counterparts, was successfully imported in vivo into yeast mitochondria and restored an ADP/ATP carrier-deficient strain (8). In the present study, we show that a hydrogenosomal protein with no homology to any reported protein from yeast was expressed stably in yeast and was targeted to its mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, several lines of evidence support a common endosymbiotic ancestry for hydrogenosomes and mitochondria, despite their distinct metabolic pathways (3,5,6). Although the origin of hydrogenosomes within ciliate and fungi lineages is debated, these lineages branch with mitochondria-containing groups and the hydrogenosomes confined therein exhibit strong similarity to ciliate and fungal mitochondria (7,8).…”
mentioning
confidence: 99%
“…Recombined homologs of PFO are present in the yeast genome (and many other fungal genomes) as sulfite reductase (200,419). ATP is exported from chytrid hydrogenosomes to the cytosol via an ATP-ADP translocase belonging to the mitochondrial carrier family (MCF) (523,545).…”
Section: Fungimentioning
confidence: 99%
“…33 Liposomes were prepared from E. coli total lipid extract and egg yolk phosphatidylcholine (Avanti Polar Lipids, Alabaster, AL) mixed in a 3:1 (w/w) ratio in 50 mM potassium phosphate buffer (pH 7.0) (KPi) at a final lipid concentration of 20 mg ml −1 . The liposomes (5 mg ml −1 in KPi buffer (pH 7.0), 5 mM ADP) and the mitochondrial membranes (1 mg of protein) were mixed.…”
Section: Preparation Of Fused Mitochondrial Membranes and Transport Amentioning
confidence: 99%